Mevlana'nın Ölümsüzlüğünün Sırrı / The Mystery of Eternality of Mowlana(His Relations With Shams) - Uğurlu, Tuğberk (Journal of History Culture and Art Research, 2016)
The Mystery of Eternality of Mowlana (His Relations With Shams) Although, religion is a guide for humanity which is sent to promote humans mundane life and keep balance of society prosperity and social relationships besides helps persons to accomplish their spritual progress and the journey to their creator, unfortunately it also went on one of the main reasons of wars that had occured during the human history and its still going on. During this long human history, humanity extremely witnessed to a lot of falsifier scholars and mystics who abused their goodwills. And thousands of intellectuals and men of religion has forgotten. However after over seven centuries Mowlana is still alive as one of the most famous Sufis and as a great leaders for eternal peace, friendship and happiness. What is the secret that in spite of all changes and progress in the ways of life and thinking, in science and technology and in the world of today his many centuries old ideas and thoughts are still valid and shining like the polar star? This article tries to answer this question. Mevlana’nın Ölümsüzlüğünün Sırrı (Şems ile ilişkisi) Din, şahısların manevi gelişimini ve kendi yaratıcılarına olan yolculuklarını tamamlayabilmelerinin yanı sıra insanların dünya hayatlarını düzenlemek, toplum refahını ve sosyal ilişkileri dengede tutmak için insanlığa gönderilmiş bir rehber olmasına rağmen maalesef uzun insanlık tarihi boyunca çıkmış savaşların temel sebeplerinden biri de olagelmiştir ve hala da devam etmektedir. Bu uzun insanlık tarihi boyunca insanlık, sahte sufilerin ve âlimlerin kendilerinin iyi niyetlerini suiistimal etmelerine fazlasıyla şahitlik etmiş ve binlerce düşünürün ve din adamlarının isimleri hafızlardan silinmişken, yedi asrı aşkın bir sürenin ardından Mevlana, en meşhur sufilerden ve ebedi huzur, dostluk ve mutluluğun ulu önderlerinden biri olarak hala hayattadır. Peki; yaşam ve düşünce tarzlarındaki, bilim ve teknolojideki bunca gelişmeye rağmen onun çok eski asırlardan gelen fikir ve düşüncelerinin hala geçerli olmasının ve bir kutup yıldızı gibi parlamasının sırrı nedir? Makalede bu sorunun cevabı aranmaktadır.